MAJELIS TAKLIM AND SOCIO-CULTURAL TRANSFORMATION OF THE SOUTH TANGERANG SOCIETY - Abd. Wahid Hasyim (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
Majelis taklim plays an essential and strategic role in the South Tangerang people's socio-cultural transformation. Amid the rapid flow of urban development, majelis taklim can still function in religious education and maintain the continuity and order of society's structure and socio-cultural system. Not only religious issues, but majelis taklim can also be a space to solve various socio-political problems. This article captures continuity and change, especially towards the expanding role of majelis taklim in South Tangerang using a qualitative method with a social history approach. In addition to the achievements, various challenges faced by majelis taklim in carrying out its socio-religious role in the modern era were also discussed. This study identifies several things. First, majelis taklim is increasingly recruiting members of various ages, education, occupation, and insight. This makes the majelis taklim more open and encourages the socio-cultural transformation of the South Tangerang people. Second, in responding to the times, majelis taklim often face administration, equipment, and communication challenges. Third, Muslims have a collective awareness about how important it is to study Islamic knowledge in majelis taklim. This motivated the community to establish majelis taklim until 2020 had reached more than 874 throughout the South Tangerang area. With the socio-religious role of majelis taklim, Muslims increasingly love their religion, deepening Islamic teachings through a religious education institution that plays an essential role in society's socio-cultural transformation